Influência do desponte de panículas de sorgo sacarino sobre a qualidade da matéria-prima e produção de bioetanol - Silva, Aline Ferreira [UNESP] (2014)
Among the different renewable raw materials available for ethanol production, the Sweet sorghum (Sorghum bicolor (L.) Moench) is a potential crop to ethanol production, because its large adaptability in different soil and climates. This use viability in industrial scale depends of several practices to optimize its energetic yield. The effects of top removal in the anthesis stage and harvest times on sweet sorghum technological quality were evaluated in this research. The experiment was arranged in a split-split-splot as a completely randomized statistical design, with four replications. Main treatments corresponded to sweet sorghum cultivars (CV147, CV198 and BRS508), secondary were the stalks management (whole and topped stalks) and tertiary were the harvest times (102 soft grain stage and 116 hard grain stage days after sowing). The quality was evaluated by the parameters: Total Soluble Solids Content (Brix), pH, Acidity, Reducing Sugars (RS), Total Reducing Sugars (TRS), Starch and Phenolic Compounds. In fermentantive process was used PE-2 yeast and was evaluated the cell viability, viability and budding of the yeasts. The α-amylase and glucoamylase were used in the clarification of the broth in the fermentation process, respectively. The delevurado wine analysis (Starch, Acidity sulfuric, Glycerol, Alcohol) and also the fermentation efficiency and productivity. The panicle removed promoted lower starch content, and the phenolic compounds in the juice, but for the other features top removed, affected negatively the technological quality of sweet sorghum.The harvest season, which provided the better raw material of quality for ethanol production, was at 102 days after sowing. The α-amylase and glucoamylase were effective in breaking, converting starch